Environmental testing. Test methods. Mounting of components, equipment and other articles for dynamic tests including shock (Ea), bump (Eb), vibration (Fc and Fd) and steady-state acceleration (Ga) and guidance Part 2-47, (29th April 1983) - British Standards Institution,
No abstract available